204k views
0 votes
Please answer the following correctly!! Thanks so much!!

Please answer the following correctly!! Thanks so much!!-example-1
Please answer the following correctly!! Thanks so much!!-example-1
Please answer the following correctly!! Thanks so much!!-example-2
Please answer the following correctly!! Thanks so much!!-example-3
Please answer the following correctly!! Thanks so much!!-example-4
User NoriSte
by
5.2k points

1 Answer

5 votes

Answer:

(1)


f(x)=3((1)/(3))^x


g(x)=3((3)/(4))^x

(2)


(8x-9-2x)(15+5x-5)=30x^2+15x-90

(3)


(x-8)^2=52

Explanation:

(1)

Calculation of f(x):

we can use exponential function formula


f(x)=a(b)^x

we can select any two points to find 'a' and 'b

At x=0 , y=3:

we can plug values


f(0)=a(b)^0


3=a(b)^0


a=3

now, we can plug it back


f(x)=3(b)^x

At x=-1 , y=9:


f(-1)=3(b)^(-1)


9=3(b)^(-1)


b=(1)/(3)

now, we can plug it back


f(x)=3((1)/(3))^x

Calculation of g(x):

we can use exponential function formula


g(x)=a(b)^x

we can select any two points to find 'a' and 'b

At x=0 , y=3:

we can plug values


f(0)=a(b)^0


3=a(b)^0


a=3

now, we can plug it back


g(x)=3(b)^x

At x=1 , y=4:


g(1)=3(b)^(1)


4=3(b)^(-1)


b=(3)/(4)

now, we can plug it back


g(x)=3((3)/(4))^x


(2)

we are given


(8x-9-2x)(15+5x-5)

we can combine like terms


(8x-2x-9)(5x+15-5)


(6x-9)(5x+10)

we can distribute it


=6x\cdot \:5x+6x\cdot \:10+\left(-9\right)\cdot \:5x+\left(-9\right)\cdot \:10


=6\cdot \:5xx+6\cdot \:10x-9\cdot \:5x-9\cdot \:10


=30x^2+15x-90

(3)

we are given


x^2-16x+12=0

Subtract both sides by 12


x^2-16x+12-12=0-12


x^2-16x=-12

We can complete square


x^2-2* 8* x=-12

we can add 8^2 both sides


x^2-2* 8* x+8^2=-12+8^2


(x-8)^2=-12+8^2


(x-8)^2=-12+64


(x-8)^2=52

User Sheng Chen
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.